An Exceptionally Preserved Specimen From the Green River Formation Elucidates Complex Phenotypic Evolution in Gruiformes and Charadriiformes - Musser, Grace; Clarke, Julia A. (Frontiers in Ecology and Evolution, 2020)
The stem lineage relationships and early phenotypic evolution of Charadriiformes (shorebirds) and Gruiformes (rails, cranes and allies) remain unresolved. It is still debated whether these clades are sister-taxa. New phylogenetic analyses incorporating Paleogene fossils have the potential to reveal the evolutionary connections of these two speciose and evolutionarily critical neoavian subclades. Although Gruiformes have a rich Paleogene fossil record, most of these fossils have not been robustly placed. The Paleogene fossil record of Charadriiformes is scarce and largely consists of fragmentary single elements. Only one proposed Eocene charadriiform-like taxon, Scandiavis mikkelseni of Denmark, is represented by a partial skeleton. Here, we describe a new species from the early Eocene Green River Formation of North America comprising a partial skeleton and feather remains. Because the skeleton lacks the pectoral girdle and forelimbs as in S. mikkelseni, only features of the skull, axial skeleton, and hind limb are available to resolve the phylogenetic placement of this taxon. These anatomical subregions initially showed features seen in Charadriiformes and Gruiformes. To assess placement of this taxon, we use a matrix consisting of 693 morphological characters and 60 taxa, including S. mikkelseni and the oldest known charadriiform taxa represented by single elements. These more fragmentary records comprise two distal humeri from the earliest Eocene Naranbulag Formation of Mongolia and the early Eocene Nanjemoy Formation of Virginia. Our phylogenetic analyses recover the new taxon and S. mikkelseni alternatively as a charadriiform or as a stem-gruiform; placement is contingent upon enforced relationships for major neoavian subclades recovered by recent molecular-based phylogenies. Specifically, when constraint trees based on results that do not recover Charadriiformes and Gruiformes as sister-taxa are used, the new taxon and S. mikkelseni are recovered within stem Gruiformes. Both Paleogene fossil humeri are consistently recovered within crown Charadriiformes. If placement of these humeri or the new taxon as charadriiforms are correct, this may indicate that recent divergence time analyses have underestimated the crown age of another major crown avian subclade; however, more complete sampling of these taxa is necessary, especially of more complete specimens with pectoral elements.